Visual Preference for Socially Relevant Spatial Relations in Humans and Monkeys - Goupil, Nicolas; Rayson, Holly; Serraille, Émilie; Massera, Alice; Ferrari, Pier Francesco; Hochmann, Jean-Rémy; Papeo, Liuba (Psychological Science, 2024)
As a powerful social signal, a body, face, or gaze facing toward oneself holds an individual’s attention. We asked whether, going beyond an egocentric stance, facingness between others has a similar effect and why. In a preferential-looking time paradigm, human adults showed spontaneous preference to look at two bodies facing toward (vs. away from) each other (Experiment 1a, N = 24). Moreover, facing dyads were rated higher on social semantic dimensions, showing that facingness adds social value to stimuli (Experiment 1b, N = 138). The same visual preference was found in juvenile macaque monkeys (Experiment 2, N = 21). Finally, on the human development timescale, this preference emerged by 5 years, although young infants by 7 months of age already discriminate visual scenes on the basis of body positioning (Experiment 3, N = 120). We discuss how the preference for facing dyads—shared by human adults, young children, and macaques—can signal a new milestone in social cognition development, supporting processing and learning from third-party social interactions.